Economic regional of beef cattle development Ciamis Regency - Perwitasari, Fitri Dian; putra, Ahmad Romadhoni Surya; Suwignyo, Bambang; Widiati, Rini (Livestock and Animal Research, 2023)
Objective: 1) To identify priority areas with Ciamis Regency that have comparative and competitive advantages 2) Availability of forages in prime priority areas.Methods: The material used cattle population data from BPS Ciamis Regency from 2016–2020. Panel data, which combines secondary data and cross-section data, were employed in this study. First, data analysis uses LQ and shift-share analysis, and two, it uses the carrying capacity of forage availability and the carrying capacity index.Results: Regional economic research results show that six sub-districts provide a comparative and competitive basis for superior commodities, namely Banjarsari, Lakbok, Cijeunjing, Cisaga, Rajadesa, and Baregbeg. These five sub-districts (Cimaragas, Sukadana, Panjalu, Panumbangan, and Sindangkasih) cannot be a base for cattle commodities but can be used as a base for other livestock. The study's findings indicate that forage is available, and the carrying capacity index forage availability has an IDD value of>2 SAFE. The Ciamis Regency has a secure green supply for expanding herds of beef cattle and can even export to other areas.Conclusions: The local government of Ciamis Regency must consider these six sub-districts an excellent commodity base, comparatively and competitively, with the carrying capacity of forage in safe conditions. The local government of Ciamis Regency must increase the number of livestock populations not only in production but also start opening up potential and conservative land for the development of grass cultivation, for example, by utilizing forest land for grass cultivation.